Effects of silylation on Ga/HZSM-5 for improved propane dehydroaromatization. (1st January 2021) - Xu, Bing; Tan, Minghui; Wu, Xuemei; Geng, Hailun; Song, Faen; Ma, Qingxiang; Luan, Chunhui; Yang, Guohui; Tan, Yisheng
Graphical abstract: Highlights: Silylated Ga/Z5 catalysts were used in propane dehydroaromatization. An appropriate SiO2 content on external surface was beneficial to cover strong BAS. Sufficient weak acid was vital to propane dehydroaromatization. The undesired cracking reaction was successfully depressed on the external surface. Extended duration of CLD process narrowed the micropore mouth size of Ga/Z5. Abstract: Dehydroaromatization of propane to high value-added aromatics, especially benzene, toluene and xylene (BTX), has attracted widespread attention. Many works have been done to improve the catalytic performance of gallium loaded HZSM-5 catalysts. However, there were few reports focused on reducing the cracked by-products, such as methane and ethylene, derived from propane cracking reaction on external Brønsted acidic sites of zeolite. Herein, chemical liquid deposition (CLD) method was adopted to passivate the external strong Brønsted acid of Ga/HZSM-5, aiming to increase the most value-added BTX production by suppressing the undesired propane cracking reaction. The content of deposited SiO2 on the external surface of zeolite was tunable by varying the amount of liquid deposition reagent and duration time of CLD process. The results showed that an appropriate content of SiO2 on external surface of catalyst was beneficial to disable the external strong Brønsted acid sites. Due to depressing the undesired propane cracking reaction, BTX selectivity of 55% with propane conversion of 49% was achieved on Ga/Z5-4Si catalyst, higher than those of Ga/HZSM-5. Otherwise, prolonging the duration time of CLD process narrowed the micropore mouth size of zeolite, which could enhance the shape selective effect of Ga/ZSM-5 to increase the proportion of para-xylene in total xylene products.